Christians in the city of Lagos - Oladipo, Caleb Oluremi (Christians in the city: studies in contemporary global Christianity, 2025)
"As well as tracing the historical development of Christianity in Lagos, this book gives readers a sense of daily life in Lagos for Christians through original ethnographic research. Incorporating interviews of Christians from six of the most influential churches in Lagos, it explores first-hand accounts of faith and practice in the city, offering a unique perspective to scholars of global Christianity"--